The use of spatial analysis in mapping the distribution of bancroftian filariasis in four West African countries - Gyapong, J.O.; Kyelem, D.; Kleinschmidt, I.; Agbo, K.; Ahouandogbo, F.; Gaba, J.; Owusu-Banahene, G.; Sanou, S.; Sodahlon, Y.K.; Biswas, G.; Kale, O.O.; Molyneux, D.H.; et al. (My University, 2002)
The geographical distribution of human infection with Wuchereria bancrofti was investigated in four West African countries (Benin, Burkina Faso, Ghana and Togo), using a commercial immunochromatographic test for filarial antigen. Efforts were made to cover each health-system implementation unit and to ensure no sampling point was > 50 km from another, but otherwise the 401 study communities were selected at random. The aim was to enable spatial analysis of the data, to provide a prediction of the overall spatial relationships of the infection. The results, which were subjected to an independent random validation in Burkina Faso and Ghana, revealed that prevalence in the adult population of some communities exceeded 70% and that, over large areas of Burkina Faso, community prevalences were between 30% and 50%. Most of Togo, southern Benin and much of southern Ghana appeared completely free of the infection. Although there were foci on the Ghanaian coast with prevalences of 10%-30%, such high prevalences did not extend into coastal Togo or costal Benin. The prevalence map produced should be useful in prioritizing areas for filariasis control, identifying potential overlap with ivermectin-distribution activities undertaken by onchocerciasis-control programmes, and enabling inter-country and sub-regional planning to be initiated. The results indicate that bancroftian filariasis is more widely distributed in arid areas of Burkina Faso than hitherto recognized and that the prevalences of infection have remained faifiy stable for at least 30 years. The campaign to eliminate lymphatic filariasis as a public-health problem in Africa will require significantly more resources (human, financial, and logistic) than previously anticipated.
Keywords: EMTREE medical terms: adolescent; adult; Africa; article; chromatography; community; controlled study; data analysis; epidemiological data; filariasis; geographic distribution; health care; health care planning; health program; human; immunochemistry; infection control; major clinical study; parasitosis; population; prevalence; public health; Wuchereria bancrofti; MeSH: Adolescent; Adult; Africa, Western; Aged; Animals; Antigens, Helminth; Elephantiasis, Filarial; Female; Health Surveys; Humans; Male; Middle Aged; Models, Statistical; Prevalence; Public Health; Residence Characteristics; Rural Health; Topography, Medical; Urban Health; Wuchereria bancrofti